Perbandingan Hasil Pemeriksaan Leukosit Pada Sedimen Urin Yang Disentrifugasi Lima Menit Dengan Variasi Waktu Tiga Menit, Tujuh Menit Dan Sepuluh Menit - arfaizah, hesti (Jurnal Laboratorium Khatulistiwa, 2022)
AbstractVariations in centrifugation time have an affect on the results of urine sediment examination. Urine sediment checks are listed in regular or routine inspections. Sediment examination is very good using morning urine because it is more concentrated and the material has not been damaged or lysis. The purpose of this study was to determine the comparison of the results of the examination of urinary leukocyte sediments that were centrifuged five minute with time variations of three minutes, seven minutes and ten minutes. The research was conducted at the Clinical Pathology Laboratory of the Faculty of Health Sciences and Technology, Binawan University. The material used morning urine. The study sample was given a 2x 60 ml urine container consisting of 2 adolescents and 4 elderly people who were willing to be respondents for urine sediment examination. The result of leukocyte analysis data are known that the average number of leukocyte cells at a time of 5 minutes is 13.14 leukocyte cells / LPB, a centrifugation time of 3 minutes is known to average 9.06 leukocyte /LPB, a centrifugation time of 7 minutes the average leukocyte cell is increasing to 17.33 leukocyte cells / LPB. The results of the urinary sediment leukocytes of the Paired T-Test can be concluded that there are significant differences in the examination of urinary leukocyte sediments with variations in centrifugation time of 3 minutes, 7 minutes and 10 minutes compared to the control time 0f 5 minutes.Â Keywords: Leukocytes Sediments; Time Centrifuges.